Qualitative exploration of determinants of active mobility and social participation in Urban neighborhoods: individual perceptions over objective factors? - Lukas Bollenbach; Martina Kanning; Christina Niermann (BMC, 2024)
Abstract Background Urban neighborhood environments play an important role in facilitating or hindering residents to engage in active mobility and social participation. However, while there is much quantitative research, in-depth knowledge that contextualizes residents' subjective perceptions of barriers and facilitators of active mobility and social participation is still insufficient. Therefore, a qualitative approach was used to collect subjectively perceived barriers and facilitators of active mobility and social participation of residents from different neighborhoods with objectively determined high vs. low walkability. Furthermore, to better understand (non) concordance of objective environmental characterizations and actual levels of behavior, low and high walkability neighborhood-specific barriers, proposed improvements, and particularities that determine (non) engagement in active mobility and social participation were explored. Methods Three focus groups (N = 6, N = 6, and N = 5) with 17 participants (7 women, 10 men) aged 21-64 (mean age 43.4 ± 14,6 years) were conducted utilizing a pre-structured interview guideline. Participants lived in 11 different neighborhoods with either high or low objectively determined walkability. The focus groups were transcribed verbatim, followed by a thematic analysis of the content with deductive and inductive code categories, utilizing the MAXQDA software. Results Notable was the consensus of many perceived barriers and facilitators of active mobility and social participation along with their assignability to the same context (points-of-interest, infrastructure; safety, communication, community; topography, physical compositions, weather, aesthetics; personal / individual attitudes, influences, evaluations). Another main finding was that high and low walkability neighborhood-specific particularities were revealed that are in contrast to some objective characterizations of walkability: For example, too high density can inhibit active mobility, and too many options can inhibit social participation. Conclusions The consensus of many barriers and facilitators of active mobility and social participation suggests that valuable synergies could be created by coordinating interventions aiming to promote both active mobility and social participation in urban neighborhoods. Also, considering subjective perceptions of residents helps to identify neighborhood-specific factors that determine (non) engagement in active mobility and social participation. The findings can help city planners and public health officials improve the promotion of active mobility and social participation in the creation of health-enhancing urban neighborhoods.